ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
This study aimed to examine the effect of Return On Investment (ROI), Debt To Equity Ratio (DER), Earning Per Share (EPS), Current Ratio  and Size of stock price Real estate and property compenies listed on the Indonesia Stock Exchange (IDX). The results showed that for the test statistic F-test, Return On Investment, Debt To Equity Ratio, Earning Per share, Current Ratio and Size jointly influence on stock prices. Partial results of hypothesis testing indicates that there is a positive effect of the Return Return On Investment, Earning Per Share and Size of the stock price. As for the Debt To Equity Ratio dan Current Ratio indicates a negative effect on stock prices. Keywords: Return On Investment, Debt To Equity Ratio, Earning Per share, Current Ratio, Size and Stock Price